The difference between young and older ducks: Amino acid, free fatty acid, nucleotide compositions and breast muscle proteome - Tiantian Gu; Mingcai Duan; Li Chen; Yong Tian; Wenwu Xu; Tao Zeng; Lizhi Lu (Food Chemistry: X)
Duck meat has a unique taste and nutritional value, but age probably affects meat quality. In this study, ducks of different ages (60-day-old, D60; 900-day-old, D900) were chosen, and the odor, taste, amino acid, nucleotide, and free fatty acid components of breast meat were evaluated to investigate the differences. The results showed that the amino acid contents of breast muscle in D900 ducks, especially in Asp (umami) and Thr (sweet), were richer than those in D60 ducks. In addition, the levels of guanosine-5′-monophosphate (GMP), inosine-5′-monophosphate (IMP), monounsaturated fatty acid (MUFA; C18:1 t), and polyunsaturated fatty acid (PUFA; C18:2) in D900 ducks were higher than those in D60 ducks. Proteomic approach was further performed to analyze the difference of breast muscle between young and older ducks in protein level. We found that 496 differentially expressed proteins (DEPs) were screened. GO and KEGG analysis mainly enriched in glycine, serine, and threonine metabolism, tyrosine metabolism, and pyruvate metabolism. Moreover, correlation analysis revealed that BPGM, ADH5, ME2, ME3, GLO1, and PDHB, were specifically correlated with amino acids, nucleotides, and free fatty acids in meat from D60 ducks, whereas only two proteins, GRHPR and COMT, showed specific correlations with amino acids, nucleotides, and free fatty acids in meat from D900 ducks. This study proposes several candidate protein biomarkers for older duck meat that should be evaluated in the future.